Role of differentiated embryo-chondrocyte expressed gene 2 in immunity - Li, Yujing; Ma, Yinan; Liu, Yang; Tang, Na; Zhang, Wenzhu; Huo, Jingru; Zhang, Di (Frontiers in Immunology, 2024)
Differentiated embryo-chondrocyte expressed gene 2 (DEC2) is a member of the basic helix-loophelix (bHLH) subfamily of transcription factors. DEC2 is implicated in tumor immunotherapy, immune system function regulation, and autoimmune diseases. DEC2 enhances Th2 cell differentiation by regulating the IL-2 and IL-4 signaling pathways and mediates the growth of B-1a cells, thereby promoting the occurrence and development of inflammatory responses. In this study, we review the reported roles of DEC2, including the regulation of immune cell differentiation and cytokine production in various cells in humans, and discuss its potential in treating autoimmune diseases and tumors.